Student motivation in the first year of University: findings from the implementation of a PBL project for a real context - Fernandes, Sandra (2021)
Student motivation is a key dimension for first year students at University. Project-based Learning (PBL) is seen as an effective teaching and learning approach to enhance student motivation and engagement. This paper describes the results from the implementation of a PBL project that was developed for a real context –a non-profit social organization that works with children. The project included, for the first time, two curricular units from the field of Psychology and Education Sciences, integrated in the first year of the study plan of the Social Education degree programme at Portucalense University, Portugal. The paper describes, on the one hand, the objectives, planning and assessment of the PBL experience from a curricular and pedagogic point of view and, on the other hand, presents students’ perceptions about their PBL experience. Data collection was based on an online survey to students, at the start of the PBL project and after its conclusion, and a content analysis of the project reports of the groups. Findings reveal the importance of the development of the project for a real context andwith a specific target audience as the main issues that enhanced studentmotivation and engagement in the courses involved in the project. Working in teams, the opportunity to develop generic competences, the stronger link between theory and practice, student resilience, teacher support and continuous feedback are also mentioned as important features of PBL that impact student motivation in the first year of University.